Aylol Revolution in the Iranian Newspaper (Ettelaat) July14th-1961 July 22nd 1962 - Youssef, Fakher Fakher (Humanities Journal of University of Zakho, 2016)
The subject of this research is the first Kurdish- Iraq War (Aylol Revolution) in the Iranian Newspaper known as Ettelaat newspaper. It is one of the most important subjects in history which talks about the relationship Iraq had with Turkey and England during the Aylol Revolution. There are many important points about it, such as the instability that occurred between Iraq and Turkey because before the revolution some of the Kurdish people left to Turkey as refugees and the relationship between the Kurds in Turkey and Kurdish refugees from Iraq became close. This was the reason the Turkish politicians became uncomfortable about the relationship because they were afraid the Kurds in north and south will rise against them and start a revolution in Turkey. The conflict between these two countries caused them to bomb each others border. The Iranian newspaper Ettelaat gave information about the problems that happened between these two countries daily. In addition to this there is also another topic discussed in this research which is the disagreement that happened between Iraq and England because of the Kurdish revolution since Iraq believed that England was helping the Kurds during this revolution but England rejected this statement.